Pollination triggers female gametophyte development in immature Nicotiana tabacum flowers - Brito, Michael S.; Bertolino, Lígia T.; Cossalter, Viviane; Quiapim, Andréa C.; DePaoli, Henrique C.; Goldman, Gustavo H.; Teixeira, Simone P.; Goldman, Maria H. S. (Frontiers in Plant Science, 2015)
In Nicotiana tabacum, female gametophytes are not fully developed at anthesis, but flower buds pollinated 12 h before anthesis produce mature embryo sacs. We investigated several pollination-associated parameters in N. tabacum flower buds to determine the developmental timing of important events in preparation for successful fertilization. First, we performed hand pollinations in flowers from stages 4 to 11 to study at which developmental stage pollination would produce fruits. A Peroxtesmo test was performed to correlate peroxidase activity on the stigma surface, indicative of stigma receptivity, with fruit set. Pollen tube growth and female gametophyte development were microscopically analyzed in pistils of different developmental stages. Fruits were obtained only after pollinations of flower buds at late stage 7 and older; fruit weight and seed germination capacity increased as the developmental stage of the pollinated flower approached anthesis. Despite positive peroxidase activity and pollen tube growth, pistils at stages 5 and 6 were unable to produce fruits. At late stage 7, female gametophytes were undergoing first mitotic division. After 24 h, female gametophytes of unpollinated pistils were still in the end of the first division, whereas those of pollinated pistils showed egg cells. RT-qPCR assay showed that the expression of the NtEC1 gene, a marker of egg cell development, is considerably higher in pollinated late stage 7 ovaries compared with unpollinated ovaries. To test whether ethylene is the signal eliciting female gametophyte maturation, the expression of ACC synthase was examined in unpollinated and pollinated stage 6 and late stage 7 stigmas/styles. Pollination induced NtACS expression in stage 6 pistils, which are unable to produce fruits. Our results show that pollination is a stimulus capable of triggering female gametophyte development in immature tobacco flowers and suggests the existence of a yet undefined signal sensed by the pistil.